Induction Strategy for Locally Advanced Thymoma - Zhang, Yang; Li, Zongjuan; Chen, Yixing; Tan, Lijie; Zeng, Zhaochong; Ding, Jianyong; Du, Shisuo (Frontiers in Oncology, 2021)
Surgery is the mainstream treatment for thymoma. Complete surgical resection (R0) plays critical role in patient prognosis. However, for locally advanced thymoma (Masaoka-Koga stages III-IVa), achieving R0 resection remains challenging. Thus, attempts to achieve successful R0 resection, are urgently required. Obviously, inductive therapy is a promising strategy towards this aim. Herein, we review the recent progress achieved in preoperative treatment in locally advance thymoma, and discuss current difficulties and future directions.